Emotionally intelligent people reappraise rather than suppress their emotions. - Megías-Robles, Alberto; Gutiérrez-Cobo, María José; Gómez-Leal, Raquel; Cabello-González, Rosario; Gross, James J.; Fernández-Berrocal, Pablo (My University, 2019)
It has long been thought that emotional intelligence (EI) involves skillful emotion regulation, but surprisingly little is known about the precise links between EI and emotion regulation. To address this gap in the literature, we examined the relation between EI—operationalised as an ability—and the use of two common emotion regulation strategies—cognitive reappraisal and expressive suppression. Seven hundred and twelve participants from a community sample in Spain were assessed on ability EI (using the MSCEIT) and emotion regulation (using the ERQ). Findings revealed that EI ability was positively associated with cognitive reappraisal and negatively associated with expressive suppression. These relationships were moderated by gender and age. The strength of the association between EI and cognitive reappraisal increased with age for men, while this strength decreased with age for women. Conversely, the strength of the association between EI and suppression decreased with age for men, but increased with age for women. These findings confirm the expectation that EI is associated with greater use of generally adaptive forms of emotion regulation (reappraisal), and lesser use of generally maladaptive forms of emotion regulation (suppression), although effect sizes were quite modest. Observed differences in the strength of associations between EI and emotion regulation may be the result of gender differences in the development of emotional skills along with cultural changes in emotional education and social norms.
Keywords: Emociones; Inteligencia; Represión (Psicología); Conocimiento; Emotional intelligence; Cognitive reappraisal; Expressive suppression